China's Rural-Urban Inequality in the Countryside - Gao, Yan (Springer Singapore, 2018)
This book approaches the issue of rural-urban inequality through fieldwork conducted in a specific township (Zuogang) in Qinggang County, part of Heilongjiang Province in northeastern China. Presenting painstaking fieldwork in a single location, it successfully illuminates fundamental aspects of the reality and the complexity of rural-urban inequality that cannot be found in macro-level studies, most of which are prepared by economists. The book offers a unique combination of rigorous economic analysis with insightful social and anthropological analysis, as well as revealing interviews with local government officials. This approach provides a rich tapestry of rural perceptions of rural-urban inequality. With in-depth analysis and empirical evidence on questions concerning the development and root causes of urban-rural disparities, the book significantly enriches our understanding of the widely discussed issue of rural-urban income inequality, but from the unique perspective of rural China. .